2018
DOI: 10.1163/22134808-00002600
|View full text |Cite
|
Sign up to set email alerts
|

Aging Impairs Audiovisual Facilitation of Object Motion Within Self-Motion

Abstract: The presence of a moving sound has been shown to facilitate the detection of an independently moving visual target embedded among an array of identical moving objects simulating forward self-motion (Calabro et al., Proc. R. Soc. B, 2011). Given that the perception of object motion within self-motion declines with aging, we investigated whether older adults can also benefit from the presence of a congruent dynamic sound when detecting object motion within self-motion. Visual stimuli consisted of nine identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The researchers report that the presentation of congruent visual signals significantly improved the precision of sound localisation in both the horizontal and vertical planes, and that this improvement was substantially more pronounced in older adults. Similarly, Roudaia et al (2018) showed that the presence of a congruent auditory cue can improve the detection of a moving visual target within an array of distractors. However, in this case older adults were found to benefit less from the added auditory information than the younger controls.…”
Section: Unspeeded Paradigms (Accuracy Enhancement)mentioning
confidence: 95%
“…The researchers report that the presentation of congruent visual signals significantly improved the precision of sound localisation in both the horizontal and vertical planes, and that this improvement was substantially more pronounced in older adults. Similarly, Roudaia et al (2018) showed that the presence of a congruent auditory cue can improve the detection of a moving visual target within an array of distractors. However, in this case older adults were found to benefit less from the added auditory information than the younger controls.…”
Section: Unspeeded Paradigms (Accuracy Enhancement)mentioning
confidence: 95%
“…These studies suggest that cross-modal cues support both auditory and visual motion perception (Cappe et al , 2009; Schmiedchen et al , 2012; Soto-Faraco et al , 2003), and modulate brain activations during motion discrimination tasks (Lewis and Noppeney, 2010; Kayser et al , 2017). Our recent studies also demonstrate that a congruent auditory cue can help identify a moving object in an environment where the observer is in self-motion (Roudaia et al , 2018), which is highly important for navigation and which underlies several critical activities of daily life, such as collision avoidance. However, overall, the evidence regarding auditory influences on visual motion processing is not entirely consistent.…”
Section: Introductionmentioning
confidence: 99%